Electro-Mechanical Stimulation of the Cochlea by Vibrating Cochlear Implant Electrodes. Issue 10 (December 2015) - Mueller, Mathias; Salcher, Rolf; Majdani, Omid; Lenarz, Thomas; Maier, Hannes
Abstract : Introduction: Electro-acoustic stimulation (EAS) of the cochlea uses the preserved residual low-frequency hearing for acoustic stimulation in combination with electrical stimulation. The acoustic low-frequency component is amplified and high-frequency hearing is enhanced by a cochlear implant (CI). In this work, the feasibility of EAS by the floating mass transducers (FMTs) firmly attached to the implanted electrode was investigated and the achieved stapes displacement was compared with sound stimulation. Methods: Experiments were performed in eight fresh human temporal bones compliant to the ASTM standard (F2504-5). Four EAS custom-made prototypes (EAS-CMP) were tested, consisting of standard MED-EL CI electrodes with Vibrant Soundbridge (VSB) FMTs or a Bonebridge (BB) FMT tightly molded to the electrode in different orientations. The stapes footplate (SFP) response to EAS-CMP stimulation and sound stimulation was measured using a Laser Doppler Vibrometer (LDV). Results: The SFP displacement amplitudes achieved by EAS-CMP stimulation were calculated to 1 VRMS FMT input and were pair-wise statistically compared between prototypes yielding no significant differences at frequencies ⩽1 kHz. At frequencies ⩽1 kHz stimulation by the BB FMT resulted in a flat and potentially highest SFP displacement amplitude of approximately −40 dB re μm at 1 VRMS input voltage. Estimated equivalent sound pressure levels achieved by the BB FMT prototype were approximately 83–90 eq. dB SPL at frequencies ⩽1 kHz. Conclusion: The feasibility of cochlear stimulation by vibrating electrodes was shown although the achieved output level at frequencies ⩽1 kHz was too low for EAS applications.